2011
DOI: 10.1121/1.3585848
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age and cochlear hearing loss on temporal fine structure sensitivity, frequency selectivity, and speech reception in noise

Abstract: Temporal fine structure (TFS) sensitivity, frequency selectivity, and speech reception in noise were measured for young normal-hearing (NHY), old normal-hearing (NHO), and hearing-impaired (HI) subjects. Two measures of TFS sensitivity were used: the "TFS-LF test" (interaural phase difference discrimination) and the "TFS2 test" (discrimination of harmonic and frequency-shifted tones). These measures were not significantly correlated with frequency selectivity (after partialing out the effect of audiometric thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
243
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(284 citation statements)
references
References 55 publications
32
243
9
Order By: Relevance
“…This confirms earlier findings that the sensitivity to temporal structure declines without accompanying elevated audiometric thresholds (e.g., Hopkins and Moore 2011). Thresholds for the LEVEL task also tended to be higher in the elderly than the young, consistently with previous finding (e.g., He et al 1998).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This confirms earlier findings that the sensitivity to temporal structure declines without accompanying elevated audiometric thresholds (e.g., Hopkins and Moore 2011). Thresholds for the LEVEL task also tended to be higher in the elderly than the young, consistently with previous finding (e.g., He et al 1998).…”
Section: Discussionsupporting
confidence: 91%
“…We then analysed correlations, as in the earlier study, between task performances. It has been reported that sensitivities to the temporal structure and intensity of stimuli decline with age (e.g., Hopkins and Moore 2011). A population including young and elderly listeners would therefore exhibit a large variability of thresholds in the monaural tasks, which would lead to improved sensitivity of the correlation analyses and provide further insights as to the roles of monaural processing in ITD or ILD discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…However, the extent to which damage in each of these entities contributes to impaired TFS processing remains difficult to quantify. Although the absence of correlation between TFS-processing measures and frequency selectivity is in agreement with the findings of, e.g., Strelcyk and Dau (2009) and Hopkins and Moore (2011), a cautionary note should be made concerning the small number of subjects used here and in previous studies. Small sample sizes impose strong limits to statistical power, and hence to the conclusions that can be drawn from not finding high correlations.…”
Section: B Correlations Between the Auditory Profile Measuressupporting
confidence: 89%
“…This correlation, together with other earlier findings on the relationship between the performance of monaural and binaural TFS tasks (Hopkins and Moore 2011;Moore et al 2012), can be interpreted as indicating that binaural TFS processing is partly determined by the efficiency of monaural TFS processing. The present study also found a significant correlation between high-rate FMDLs and high-rate AMDLs.…”
Section: Correlation Among Psychoacoustic Measuressupporting
confidence: 81%